A safe space for self-expansion: Attachment and motivation to engage and interact with the story world. (November 2019) - Silver, Nathan; Slater, Michael D.
Insecure attachment places enduring limitations on one's ability to satisfy important intrinsic needs. An increasing body of literature suggests that such barriers may motivate engagement with stories such as absorption into fictional worlds, sharing experiences and forming relationships with characters, and even pursuing vicarious satisfaction of unmet needs. Moreover, this sort of engagement has been demonstrated to drive narrative influence, further suggesting that barriers to intimacy in relationships such as those characterized by insecure attachment may render one more susceptible to the influence of entertainment media. A cross-sectional survey ( N = 1, 039) revealed an interaction between the anxiety and avoidance dimensions of attachment wherein avoidance was negatively associated with parasocial relationships, boundary expansion, and transportability, as well as self-reported proclivities to reflect on and be impacted by story-based movies and television when anxiety was low but was associated with increased engagement when anxiety was high. The potential interplay between attachment and narrative influence is discussed with respect to targeting and tailoring media literacy and narrative-based interventions.